Molecular investigation of zoonotic genotypes of Giardia intestinalis isolates in humans, dogs and cats, sheep, goats and cattle in Araçatuba (Sãoo Paulo State, Brazil) by the analysis of beta-giardin gene fragments - Godoy, Elenir Alves Macedo de; Santos Júnior, Juares Elias; Belloto, Marcus Vinícius Teresa; Moraes, Marcus Vinícius Proença de; Cassiano, Gustavo Capatti; Volotão, Aline Cardoso Caseca; Luvizotto, Maria Cecília Rui [UNESP]; Carareto, Claudia Marcia Aparecida [UNESP]; Silva, Mônica Cristina de Moraes; Machado, Ricardo Luiz Dantas (MDPI, 2013)
In the period from July 2009 to October 2010, fecal samples from 61 animals and 154 humans from the municipality of Aracatuba (São Paulo State, Brazil) were studied. Fecal samples from animals were collected in the Municipal Animal Shelter and the Veterinary Hospital of the Universidade Estadual Paulista. Human fecal specimens were collected in playschools in the outskirts of the city by the private network of clinical analysis laboratories of the municipal. Diagnosis was done by optical microscopy using the Faust and Hoffmann, Pons and Janer techniques. The genotypes of Giardia intestinalis were characterized by PCR-RFLP and confirmed by sequencing the ß-giardin gene. Human specimens were positive in 25.3% (39/154) of the cases with 26.8% (36/134) of the specimens from children and 15% (3/20) from adults being positive. The frequency of G. intestinalis among the animals was 23.0% (14/61). A total of 32 isolates of G. intestinalis obtained from human feces and six from dogs and cats were characteristic of the A genotype (AI and AII/AIII). The results of this study in respect to frequency of giardiasis are similar to reported in most studies in Brazil. The prevalence observed in animal populations conforms to worldwide infection rates. G. intestinalis genotypes considered zoonotic were detected in both pets and humans from the city of Aractuba, suggesting a possible zoonotic transmission of the parasite in the northwestern region of São Paulo State. The absence of these genotypes in farm animals may imply that they are not involved in the chain of transmission to humans in this region.
Keywords: Giardia; zoonosis; genotypes; epidemiology; Brazil